If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(t + -1) = 9t + 6 Reorder the terms: 3(-1 + t) = 9t + 6 (-1 * 3 + t * 3) = 9t + 6 (-3 + 3t) = 9t + 6 Reorder the terms: -3 + 3t = 6 + 9t Solving -3 + 3t = 6 + 9t Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-9t' to each side of the equation. -3 + 3t + -9t = 6 + 9t + -9t Combine like terms: 3t + -9t = -6t -3 + -6t = 6 + 9t + -9t Combine like terms: 9t + -9t = 0 -3 + -6t = 6 + 0 -3 + -6t = 6 Add '3' to each side of the equation. -3 + 3 + -6t = 6 + 3 Combine like terms: -3 + 3 = 0 0 + -6t = 6 + 3 -6t = 6 + 3 Combine like terms: 6 + 3 = 9 -6t = 9 Divide each side by '-6'. t = -1.5 Simplifying t = -1.5
| (1/4x+2/5)+(3/4x-4/5) | | -0.60h=-28 | | 15/7.5 | | 0.10(y-5)+0.12y=0.02y-0.01(40) | | 3(2x-1)=-2(x-4) | | 3u+7/2=8 | | x-2(3-4x)=12 | | 3u+7/2 | | 3y+2/5=4y+1/5 | | -9-3x=15 | | 8r+6=9r | | 4x^3-150x^2+900x-450=0 | | 5(2z+4)=170 | | 2n^3-14n^2=0 | | 1.6x=-9.12 | | 6+8r-5=1+7r+r | | (3*3)-(2(11-8)*2(11-8))=36x | | 5=6z-30-19 | | 6n^2+24n-360=0 | | 4n-3=3n+7 | | 45a^2-320a-320=0 | | 8z-11(z-2)=-8 | | 3/6x+6=4/2x | | 10-8x=5+17x | | 8z-11z-22=-8 | | 0.4(5k+35)-8=26 | | 27=7y+6 | | -4+5(x-2)=-16 | | 8+7(n+5)=4(8-n) | | 7-4v=6-6v+2v | | 1+2(d+1)=3+8(b+9) | | 7-4z-12=23 |